Pernikahan Dini dan Marginalisasi Perempuan Nuaulu - Johan Tanamal; Lodewyk Nahuway (Univiversitas Dr. Djar Wattiheluw, 2022)
This study was almet at learning the view of Nuaulu tribe toward the early marriage of women also to know how women of Nuaulu which is still and education can avoid the early marriage. The result showed that 2 major culture factors influenced the early marriage, are Nuaulu people tend to consider the women in the lowest position in the their tribe also people of nuaulu are not well educated. The influenced their way of the thinking and prompted the early marriage within their tribe. Meanwhile, being kept marginalize by the situation such as when the girl is labled as dowry, it is consider that the girl can produce the money to help her parents by being married. Moreover, after the girl have their first period, they will Pinamoukan. Therefore the solution to this early marriage is the women of Nuaulu must get an education to a high level.